DESAIN APLIKASI PEMBELAJARAN MATEMATIKA ENVEMATH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN MINAT BELAJAR SISWA (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
The purpose of this study is to develop and evaluate the validity of the mathematics learning application "EnveMath" to improve students' critical thinking ability and learning interest. The type of research is research and development with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) with a focus on the initial three stages, namely analysis, design, and development. Data collection techniques used interviews, observations, questionnaires, material expert validation questionnaires, and media expert validation questionnaires. The data sources in this study are students of grade VIII C SMP Negeri 11 Yogyakarta, two material expert validators, and two media expert validators. Meanwhile, the object of this research is the curriculum, learning model, learning resources, and student characteristics. Based on the results of the research that has been carried out, it shows that (1) students' critical thinking skills and learning interest still tend to be low, so it is necessary to analyze the need for the development of mathematics learning media to improve students' critical thinking skills and learning interests, (2) the researcher developed an android-based EnveMath mathematics learning application on the Opportunity material which contains a set menu of learning activities, instructions for use,  and application information, (3) the validation results show that the EnveMath application obtained an average score of 53.5 with very valid criteria from material experts and an average score of 47.5 with valid criteria from media experts. Thus, this learning application meets the criteria of good validity and is suitable for use so that research can be continued to the implementation and evaluation stage.
Keywords: Development Research; Learning Application; Validity of Learning Media